A systematic literature review on digital literacy, employability, and innovative work behavior: emphasizing the contextual approaches in HRM research - Caroline, Angela; Coun, Martine J. H.; Gunawan, Agus; Stoffers, Jol (Frontiers in Psychology, 2025)
Knowledge Society 5.0 and Industry 5.0 require workers with adaptable employability skills and who engage in innovative work behavior that help companies to create innovative products and processes that are difficult for competitors to imitate. Extant research examines employability, and innovative work behavior, but there are still few articles that include digital literacy in their study. In fact, digital literacy is closely related to human resources in the new workforce whose daily activities are closely related to digital technology. Through bibliometric analysis and a systematic literature review of the interplay among digital literacy, employability, and innovative work behavior we synthesize research trends, measurements, theoretical frameworks, and conceptual models on these topics. In addition, some contextual considerations will be utilized to ensure accurate data interpretation. Findings suggest that there is no generic measure of digital literacy, especially in business contexts, that links this concept to either employability or innovative work behavior. Digital literacy is particularly important to increase employability and stimulate both innovative behavior and performance. Future research should explore these topics using various methodologies and theoretical frameworks, combining them with multiple perceptions across workers and countries, especially considering the pace of technological development.